Country‐Specific vs. Common Birthweight‐for‐Gestational Age References to Identify Small for Gestational Age Infants Born at 24–28 weeks: An International Study. Issue 5 (16th May 2016) - Martin, Lisa J.; Sjörs, Gunnar; Reichman, Brian; Darlow, Brian A.; Morisaki, Naho; Modi, Neena; Bassler, Dirk; Mirea, Lucia; Adams, Mark; Kusuda, Satoshi; Lui, Kei; Feliciano, Laura San; et al.
Abstract: Background: Controversy exists as to whether birthweight‐for‐gestational age references used to classify infants as small for gestational age (SGA) should be country specific or based on an international (common) standard. We examined whether different birthweight‐for‐gestational age references affected the association of SGA with adverse outcomes among very preterm neonates. Methods: Singleton infants ( n = 23 788) of 24 0 –28 6 weeks' gestational age in nine high‐resource countries were classified as SGA (<10th centile) using common and country‐specific references based on birthweight and estimated fetal weight (EFW). For each reference, the adjusted relative risk (aRR) for the association of SGA with composite outcome of mortality or major morbidity was estimated. Results: The percentage of infants classified as SGA differed slightly for common compared with country specific for birthweight references [9.9% (95% CI 9.5, 10.2) vs. 11.1% (95% CI 10.7, 11.5)] and for EFW references [28.6% (95% CI 28.0, 29.2) vs. 24.6% (95% CI 24.1, 25.2)]. The association of SGA with the composite outcome was similar when using common or country‐specific references for the total sample for birthweight [aRRs 1.47 (95% CI 1.43, 1.51) and 1.48 (95% CI 1.44, 1.53) respectively] and for EFW references [aRRs 1.35 (95% CI 1.31, 1.38) and 1.39 (95% CI 1.35, 1.43) respectively]. Conclusion: Small for gestational age is associated with higher mortality and morbidity in infants born <29 weeks' gestational age. Although common and country‐specific birthweight/EFW references identified slightly different proportions of SGA infants, the risk of the composite outcome was comparable.